2009
DOI: 10.1097/shk.0b013e3181971f47
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant Cerebralcare Granule Attenuates Cerebral Microcirculatory Disturbance During Ischemia-Reperfusion Injury

Abstract: Cerebralcare Granule (CG) is a compound Chinese medicine used for treatment of headache and dizziness associated with cerebrovascular diseases. To clarify the mechanism underlying the clinical outcome of CG, this study investigated the effects of CG on the structure and function of cerebral microvasculature during I/R injury. A total of 138 Mongolian gerbils were included and divided into four groups, each composed of 36 or 30 animals, for evaluating various parameters of concern. A skull window was prepared f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 40 publications
4
28
0
Order By: Relevance
“…The improved NA associated with YXQN, but not with nocturnal levodopa, may be attributed to differences in the pharmacologic actions on dopamine receptor subtypes or the effects of YXQN on other neurotransmitter systems [15]. The UPDRS scores improved slightly after YXQN administration (Table 2), and the observed benefits might be caused by the sleep effects, rather than direct motor effects, in patients with PD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The improved NA associated with YXQN, but not with nocturnal levodopa, may be attributed to differences in the pharmacologic actions on dopamine receptor subtypes or the effects of YXQN on other neurotransmitter systems [15]. The UPDRS scores improved slightly after YXQN administration (Table 2), and the observed benefits might be caused by the sleep effects, rather than direct motor effects, in patients with PD.…”
Section: Discussionmentioning
confidence: 99%
“…As a CM compound for treating headache and dizziness associated with serious sleep disturbances, Yang-Xue-Qin-Nao granules (YXQN) attenuate cerebral microcirculatory disturbances during ischemia-reperfusion injury in vivo [15], which might improve the sleep dysfunction in PD patients. YXQN (Tianjin Tasly Pharmaceutical Co. Ltd., Tianjin, China) is a newly developed compound medicine that was approved in 1996 by the China State Food and Drug Administration for the treatment of headache and dizziness associated with cerebrovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, a clinical study of post-stroke patients showed that CG use led to greater cognitive improvement than aspirin (Zhao et al, 2017). Other groups demonstrated that ischemia-induced cognitive impairment could be ameliorated by CG (Xu et al, 2009; Sun et al, 2010; Zhang X. X. et al, 2016). In addition, CG has been widely used to treat chronic cerebral circulation insufficiency (Xiong et al, 2011; Wu C. H. et al, 2013), which is often associated with cognitive impairment (Hirai, 1991).…”
Section: Introductionmentioning
confidence: 98%